If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8(3x + -5) = 7x + -28 Reorder the terms: 3x + 8(-5 + 3x) = 7x + -28 3x + (-5 * 8 + 3x * 8) = 7x + -28 3x + (-40 + 24x) = 7x + -28 Reorder the terms: -40 + 3x + 24x = 7x + -28 Combine like terms: 3x + 24x = 27x -40 + 27x = 7x + -28 Reorder the terms: -40 + 27x = -28 + 7x Solving -40 + 27x = -28 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -40 + 27x + -7x = -28 + 7x + -7x Combine like terms: 27x + -7x = 20x -40 + 20x = -28 + 7x + -7x Combine like terms: 7x + -7x = 0 -40 + 20x = -28 + 0 -40 + 20x = -28 Add '40' to each side of the equation. -40 + 40 + 20x = -28 + 40 Combine like terms: -40 + 40 = 0 0 + 20x = -28 + 40 20x = -28 + 40 Combine like terms: -28 + 40 = 12 20x = 12 Divide each side by '20'. x = 0.6 Simplifying x = 0.6
| 4x-24-8x=4x | | 10n-29=61 | | (-4-3)(-3+6)-54= | | (6x^2/y)^-2 | | 6x-2=9x-20 | | 2(-8+6)=7(-8)-20 | | 9z=18-45 | | -49x^2-49x-12=0 | | 7(x+3)=7x-42 | | 5*1/5a=a | | 9x=24x+75 | | 9x=24+75 | | -7x+y=-20 | | 412=(x^2)/x | | 8g-4g=24 | | 30-[2+8x-4(x+3)]=-5(5x-4)-[8(x-1)-20x+15] | | 3/5k=21/7 | | Y-2=0.5(x+3) | | 9+3c=2c-10 | | 14=21x | | -35x+30+5=-10 | | y=2x^3+3x^2-36x+10 | | (q^2-4q+24)/(q+2) | | 2x-2-8=0 | | 5=x/2 | | m^2-6m=-5m | | 3(8x+2)=23x+9 | | 6a^2=8a+5a^2-15 | | 6x-3+2x=7x+5 | | 5x+5=3x+31 | | 3x^2-18-60= | | (0.111)=0.5 |